Impressions about Security: Salvador Residents Perspective in Relation to their Neighborhoods Security - Tânia Benevides (2021)
This article seeks to analyze the perception of the Salvador City residents, Bahia State Capital, in Brazil, in relation to the elements that can promote the biggest security to the 163 Bahia Capital neighborhoods. The study starts from the research question: what is the Salvador residents' perception in relation to the factors that can bring more security to their neighborhood? The general objective is to analyze the Salvador inhabitant's impressions as elements that can lead to increased security in their respective neighborhoods. To achieve this objective, the methodological path is based on a qualitative research, initiated from an exploratory phase, elaborated from the bibliographic and documentary research, followed by the field research, through the application of the data collection instrument, which resulted in the application of 15,260 questionnaires in all neighborhoods of the capital, between the years 2018 and 2020. This study is part of a broader survey, carried out by a group of researchers who are part of a larger project called QUALISalvador, whose objective is to produce and disseminate knowledge about the reality of Salvador. The clipping of this article is the question 56 “What could bring security to your neighborhood?” of the questionnaire. The data used in this analysis are derived from studies carried out by the subgroup that assesses the influence of public security and the residents' perception of security / insecurity. As a main result, it was evident that, in the perception of the Salvadorans, what could bring more security to their neighborhoods is the increase in State actions, through ostensive policing and rounds in the neighborhoods. Based on this result, it is possible to reflect on the impact of the State's reprehensible performance, leading to reflection on the intersectoral aspects of security, which go far beyond police action, ensuring, even, the right to the city and the guarantee of fundamental rights.